Pendapatan Rendah Vs Pendapatan Tinggi : Mengatasi Ketimpangan Pendapatan di Kota Madiun - Miftahul Fauziyah Hanifah; Nasikh Nasikh (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
The purpose of this research is to analyze the causes and efforts to overcome income inequality in Madiun City by looking at the relationship between age, education, experience, and working hours with the income of the population. The quantitative method is the approach chosen with the collection process data through surveys and data processing using the multiple linear regression analysis method. The accuracy of the regression model used was analyzed through the classical assumption test by utilizing data cross section taken in 2021. The population used was 90.334 residents of Madiun City aged 15 years and over with the provision that they were working. The sample used for the study was 100 respondents taken from three sub-districts in Madiun City, namely Kartoharjo District, Manguharjo District, and Taman District. Method was simple random sampling chosen as the technique used to take the sample. The data primary used in the study were obtained through direct collection with questionnaires as a data collection tool and the secondary data used were obtained from journals, books, and government publications. The results obtained from the analysis state that there is a positive but not significant effect between age and working hours with income, as well as a positive and significant effect between education and experience with income so that it can be used as a reference in planning strategies to overcome inequality in Madiun City.